Beyond Screen Time: Identity Development in the Digital Age. Issue 3 (2nd July 2020) - Granic, Isabela; Morita, Hiromitsu; Scholten, Hanneke
Abstract: We are in the midst of a global transition in which digital "screens" are no longer simply entertainment devices and distractions; rather, adolescents are currently living in a hybrid reality that links digital spaces to offline contexts. Yet, psychological scientists studying the mental health impact of digital experiences largely focus on correlations with "screen time, " leading to oversimplified and atheoretical conclusions. We propose an alternative, functional approach to studying adolescent mental health in the digital age, one that examines why and how digital media affect adolescent development. Specifically, we suggest that understanding identity development—the core developmental task of adolescence—can help pinpoint the digital experiences that contribute to healthy versus problematic mental health outcomes. We have four objectives: (1) integrate principles from clinical and personality psychology with developmental theory to present a theoretical framework for investigating narrative identity; (2) show how this framework provides a useful lens for evaluating the impact of digital media on adolescents; (3) suggest a set of novel hypotheses that specify what kinds of digital contexts and experiences lead to healthy versus problematic mental health outcomes; and (4) propose a detailed research agenda that tests these hypotheses.